The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1128/jb.00598-09
|View full text |Cite
|
Sign up to set email alerts
|

A Unique β-1,2-Mannosyltransferase of Thermotoga maritima That Uses Di- myo -Inositol Phosphate as the Mannosyl Acceptor

Abstract: In addition to di-myo-inositol-1,3-phosphate (DIP), a compatible solute widespread in hyperthermophiles, the organic solute pool of Thermotoga maritima comprises 2-(O-␤-D-mannosyl)-di-myo-inositol-1,3-phosphate (MDIP) and 2-(O-␤-D-mannosyl-1,2-O-␤-D-mannosyl)-di-myo-inositol-1,3-phosphate (MMDIP), two newly identified ␤-1,2-mannosides. In cells grown under heat stress, MDIP was the major solute, accounting for 43% of the total pool; MMDIP and DIP accumulated to similar levels, each corresponding to 11.5% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Moreover, there are several examples of solutes from hyperthermophiles whose levels respond both to heat and salt stress (31). For instance, ␣-glutamate accumulates in Thermotoga maritima in response to these two types of stress (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there are several examples of solutes from hyperthermophiles whose levels respond both to heat and salt stress (31). For instance, ␣-glutamate accumulates in Thermotoga maritima in response to these two types of stress (27).…”
Section: Discussionmentioning
confidence: 99%
“…The data reveal a trend toward specialization of roles in thermoadaptation and osmoadaptation. Indeed, mannosylglycerate and diglycerol phosphate typically accumulate in response to increased NaCl concentration in the growth medium, whereas the levels of DIP and derivatives consistently increase at supraoptimal growth temperatures (11,16,17,27,31). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the bacterium Calderobacterium hydrogenophilum polyamine compounds stabilize the 70S initiation complex of ribosomes (Mikulik and Anderova 1994). Many temperature studies in the Thermotogae have focused on the accumulation of these organic compounds and polyamines and the elucidation of their biosynthetic pathways in T. maritima and the more moderate thermophile Petrotoga miotherma (Zellner and Kneifel 1993;Jorge et al 2007;Rodrigues et al 2009;Oshima et al 2011;Rodionova et al 2013). Several compatible solutes have so far been found only in thermophiles, including di-myoinositol phosphate, mannosyl-di-myo-inositol phosphate, mannosylglyceramide, and diglycerol phosphate (Borges et al 2010;Gonçalves et al 2012), and novel thermophilic solutes continue to be identified (Jorge et al 2007;Rodrigues et al 2009).…”
Section: Compatible Solutes: the Power Of Redundancymentioning
confidence: 99%
“…When the ability to synthesize di-myo-inositol phosphate was removed from Thermococcus kodakarensis by deleting a key synthesis gene, the growth of this archaeon was unaffected, and aspartate accumulated as an alternative compatible solute (Borges et al 2010). In the Thermotogae, multiple solutes accumulate under stress conditions (Jorge et al 2007;Rodrigues et al 2009). This suggests that although the role compatible solutes play in thermal protection is not fully understood, there is functional redundancy among the solutes.…”
Section: Compatible Solutes: the Power Of Redundancymentioning
confidence: 99%